The Position of Foreign Citizens in Land Lease Agreements - PRADYAN, I Gusti Ngurah Agung Krisna; SUWITRA, I Made; WIJAYA, Ketut Kasta Arya (Protection: Journal Of Land And Environmental Law, 2025)
The purpose of this research is to analyze the validity of lease transfer agreements from Foreign Nationals to Indonesian Citizens and to examine the legal consequences of land lease agreements by Foreign Nationals. The type of legal research used is normative legal research, with statutory and analytical approaches. This legal research utilizes two types of legal materials, namely primary legal materials and secondary legal materials. The research results indicate that the validity of the lease transfer agreement by a foreign national with a Visa on Arrival (VoA) in Supreme Court Decision No. 2099 K/Pdt/2017 is deemed invalid because foreign nationals do not meet the legal capacity requirements as per Article 1320 of the Civil Code in conjunction with Article 45 of the UUPA. The temporary nature of the Visa on Arrival (VoA) does not satisfy the requirement of being domiciled in Indonesia, which necessitates a valid and ongoing residence permit. The legal consequences of this agreement are that it can be annulled due to the failure to meet the subjective requirements in Article 1320 of the Civil Code. This means that the agreement remains formally valid but can be annulled by the aggrieved party through a court ruling.